REGIONAL ECONOMIC DEVELOPMENT AND THE CASE OF WALES: THEORY AND PRACTICE AND PROBLEMS OF STRATEGY AND POLICY. (2022) - Bradbury, Jonathan; Davies, Andrew
Abstract: The article assesses economic development strategy in Wales since devolution. It considers theoretical views on success or failure of devolution to realise economic benefit, and reviews existing explanations of Wales' lack of success in changing its position relative to other UK territories. The article develops a novel critique first of overall economic development strategy, suggesting problems of coherence, consistency and methods of implementation. It then critiques three policies that have had the potential to realise development strategy - transport, renewable energy and public procurement - again revealing problems of coherence, consistency, implementation and governance.